The impact of nursing-led emotional preparation on mental health after total hip arthroplasty - Ripoll-Romero, Elisabet; Agüera, Zaida; Puig-Llobet, Montserrat; Galimany-Masclans, Jordi (Frontiers in Psychology, 2025)
BackgroundPostoperative anxiety and depression are common following total hip arthroplasty (THA) and can negatively affect recovery. While pharmacological management is standard, non-pharmacological interventions may offer additional benefits without adverse side effects.ObjectiveTo assess the effectiveness of a nurse-led video-based intervention on anxiety and depression symptoms and perceived quality of life in patients undergoing THA, compared to standard care.MethodsA quasi-randomized controlled trial was conducted with 131 participants undergoing elective THA, randomly assigned to an intervention group (IG; n = 67) receiving a preoperative nursing intervention focused on emotional preparation and information, and a control group (CG; n = 64) receiving usual care. Psychopathological symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS), and quality of life was measured using the EQ-5D-5L. Assessments occurred at baseline (pre-surgery), post-intervention (hospital discharge), and one-month follow-up. General Linear Model (GLM) analyses were used for within- and between-group comparisons.ResultsNo significant differences in anxiety or depression symptoms were found between baseline and hospital discharge in either group. Both groups showed significant improvement in HADS scores and all EQ-5D-5L dimensions at one-month follow-up. Although the IG initially appeared to show greater improvement in depression symptomatology and in the ‘usual activities’ dimension compared to the CG, these differences were no longer statistically significant after adjusting for baseline depression. No other significant between-group differences were observed.ConclusionThe nurse-led video-based intervention did not produce immediate emotional benefits but was associated with improved functional recovery at 1 month; however, it has not been shown to be more effective than usual care. These findings suggest that targeted nursing interventions may support postoperative recovery, particularly in functional outcomes, while emotional effects remain inconclusive and warrant further investigation. Importantly, the video format offers a more sustainable and cost-effective approach compared to printed materials, reducing the need for physical handouts while maintaining structured patient education.